To <span>transform the quadratic equation into the equation form (x + p)2 = q we shall proceed as follows:
3+x-3x^2=9
putting like terms together we have:
-3x^2+x=6
dividing through by -3 we get:
x^2-x/3=-2
but
c=(b/2a)^2
c=(-1/6)^2=1/36
thus the expression will be:
x^2-x/3+1/36=-2+1/36
1/36(6x-1)</span>²=-71/36
the answer is:
1/36(6x-1)²=-71/36
Answer:
The equation of the quadratic function shown is;
x^2+ 2x -3
Step-by-step explanation:
Here in this question, we need to know the quadratic equation whose graph was shown.
The key to answering this lies in knowing the roots of the equation.
The roots of the equation are the solution to the quadratic equation and can be seen from the graph at the point where the quadratic equation crosses the x-axis.
The graph crosses the x-axis at two points.
These are at the points x = -3 and x = 1
So what we have are;
x + 3 and x -1
Multiplying both will give us the quadratic equation we are looking for.
(x + 3)(x-1) = x(x -1) + 3(x-1)
= x^2 -x + 3x -3 = x^2 + 2x -3
Are you wanting to solve for x? If so:
4x + 7 = 35
We want to isolate the variable, so subtract 7 from both sides. You will get:
4x = 28
Now, divide each side by 4 to get X by alone. This will give you:
x = 7
I hope this helped.